2011
DOI: 10.1111/j.1365-313x.2011.04719.x
|View full text |Cite
|
Sign up to set email alerts
|

Barley mildew and its elicitor chitosan promote closed stomata by stimulating guard‐cell S‐type anion channels

Abstract: SUMMARYStomatal closure is known to be associated with early defence responses of plant cells triggered by microbeassociated molecular patterns (MAMPs). However, the molecular mechanisms underlying these guard-cell responses have not yet been elucidated. We therefore studied pathogen-induced changes in ion channel activity in Hordeum vulgare guard cells. Barley mildew (Blumeria graminis) hyphae growing on leaves inhibited light-induced stomatal opening, starting at 9 h after inoculation, when appressoria had d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 76 publications
1
57
0
Order By: Relevance
“…3; Supplemental Fig. S1) 1989; Pei et al, 1997;Munemasa et al, 2007;Koers et al, 2011;Xue et al, 2011;Hua et al, 2012). YEL was reported to activate anion channel in root cells (Wu et al, 2011).…”
Section: Cpk6 Positively Functions In Activation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…3; Supplemental Fig. S1) 1989; Pei et al, 1997;Munemasa et al, 2007;Koers et al, 2011;Xue et al, 2011;Hua et al, 2012). YEL was reported to activate anion channel in root cells (Wu et al, 2011).…”
Section: Cpk6 Positively Functions In Activation Ofmentioning
confidence: 99%
“…Elicitors derived from microbial surface mimic pathogen attack and induce stomatal closure in various plant species such as Solanum lycopersicum (Lee et al, 1999), Commelina communis (Lee et al, 1999), Hordeum vulgare (Koers et al, 2011), and Arabidopsis (Arabidopsis thaliana; Melotto et al, 2006;Khokon et al, 2010). Yeast elicitor (YEL) induces stomatal closure in Arabidopsis (Klüsener et al, 2002;Khokon et al, 2010;Salam et al, 2013).…”
mentioning
confidence: 99%
“…[1][2][3][4][5] CHT-induced stomatal closure such as ABA-and MeJA-induced stomatal closure is accompanied by ROS production and [Ca 2þ ] cyt oscillation in guard cells. [1][2][3] In Pisum sativum, CHT-induced ROS production is mediated by NADPH oxidases, 3) whereas CHTinduced ROS production is mediated by SHAM-sensitive peroxidases in Arabidopsis thaliana.…”
mentioning
confidence: 99%
“…Chitosan also induces the accumulation of phytoalexins in tissues of host plants, decreasesthe total content and changes the composition of free sterols producing adverse effects on infesters, activated chitinases, beta-glucanases, and lipoxygenases, and stimulates the generation of reactive oxygen species (Vasyukova et al 2001). Barley mildew and its elicitor chitosan promotes closed stomata by stimulating guard-cell S-type anion channels (Koers et al 2011). It has also been reported that the addition of chitosan, chitosan oligosaccharide and alginate oligosaccharide to the culture of P. ginseng hairy roots caused inhibition of growth but total ginseng saponin accumulated slightly with an increase in elicitor concentration .…”
Section: Oligosaccharidementioning
confidence: 99%